2016
DOI: 10.1016/j.bbamem.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-grained simulations of hemolytic peptide δ-lysin interacting with a POPC bilayer

Abstract: δ-lysin, secreted by a Gram-positive bacterium Staphylococcus aureus, is a 26-residue membrane active peptide that shares many common features with antimicrobial peptides (AMPs). However, it possesses a few unique features that differentiate itself from typical AMPs. In particular, δ-lysin has zero net charge, even though it has many charged residues, and it preferentially lyses eukaryotic cells over bacterial cells. Here, we present the results of coarse-grained molecular dynamics simulations of δ-lysin inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 72 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…These restrictions can be solved by the use of simplified coarse-grained (CG) models that nowadays have reached good agreement with atomically detailed simulations. Particularly, the MARTINI CG model has been used in several studies for the simulations of AMPs interacting with lipid bilayers, and has shown the formation of pores in some cases [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…These restrictions can be solved by the use of simplified coarse-grained (CG) models that nowadays have reached good agreement with atomically detailed simulations. Particularly, the MARTINI CG model has been used in several studies for the simulations of AMPs interacting with lipid bilayers, and has shown the formation of pores in some cases [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…One needs to address both the role of polypeptide sequence and salt in the medium. There are coarse-grained studies on polymer-membrane systems [17][18][19][20][21][22] where the structures of lipids, water, and amino acids are approximated by mapping several atoms into an equivalent particle in order to enable to study much larger systems and longer simulations. Martini coarse-grained force field provide important information on localization and translocation of CPPs across membranes.…”
mentioning
confidence: 99%